2013
DOI: 10.1080/03630242.2013.817505
|View full text |Cite
|
Sign up to set email alerts
|

Does Pilates-Based Exercise Improve Postural Alignment in Adult Women?

Abstract: A randomized, controlled trial was conducted to determine the effect of Pilates-based exercise on postural alignment. Seventy-four adult women (mean age ± SD, 34.9 ± 16.4 years) were randomized to a Pilates-based mat class (n = 40) or a control group (n = 34). Pilates-based exercise participants were taught the Initial Mat of Body Control Pilates for 6 months, twice a week, for 60 minutes per session; the control group received no exercise intervention. Repeated measurements were performed at baseline, 3 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
14

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 32 publications
0
35
0
14
Order By: Relevance
“…However, the beneficial effects of other related forms of physical activity on the body and health have been thoroughly discussed. cruz-Ferreira et al [7] presented C7 -spinous process of the seventh cervical vertebra KP -apex of thoracic kyphosis PL -transition from kyphosis to lordosis LL -apex of lumbar lordosis S1 -transition from lumbar lordosis to the sacral spinal cord the effects of Pilates exercises in women, finding an improvement in some of the postural alignment measures (frontal alignment of the shoulder and sagittal alignment of the head and pelvis). This group suggested that the significant improvement in the sagittal alignment of the head may imply that 6 months of Pilates-based exercise can enhance sagittal alignment of the cervical or thoracic spine.…”
Section: Discussionmentioning
confidence: 99%
“…However, the beneficial effects of other related forms of physical activity on the body and health have been thoroughly discussed. cruz-Ferreira et al [7] presented C7 -spinous process of the seventh cervical vertebra KP -apex of thoracic kyphosis PL -transition from kyphosis to lordosis LL -apex of lumbar lordosis S1 -transition from lumbar lordosis to the sacral spinal cord the effects of Pilates exercises in women, finding an improvement in some of the postural alignment measures (frontal alignment of the shoulder and sagittal alignment of the head and pelvis). This group suggested that the significant improvement in the sagittal alignment of the head may imply that 6 months of Pilates-based exercise can enhance sagittal alignment of the cervical or thoracic spine.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the sample, three studies were conducted predominantly with young adult women 7,18,19 . Regarding quality, three studies were highly rated, being these conducted with more than 30 individuals 7,18,20 , however, only one had exclusively chosen female older adults 20 . Donahoe-Fillmore et al 19 also focused on the young adult age group, but conducted a low-quality study, with only 11 individuals, and we must be careful when interpreting the results of their study.…”
Section: Discussionmentioning
confidence: 99%
“…In the intervention, three studies adopted Pilates Method exercises on the floor 7,18,19 and only one study added equipment 20 . The preference may be due to low cost, ease of performance regarding physical space, and the fact that the exercises can be taught in larger groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations